2022
DOI: 10.1037/sah0000372
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of interventions on cognitive, behavioral, and affective public stigma around mental illness: A systematic meta-analytic review.

Abstract: For individuals with mental disorders, public stigma around mental illness exacerbates maladjustment and reluctance to seek treatment, contributing to poor quality of life beyond the effects of the disorder itself. Previous research demonstrates small, albeit significant, effect sizes for stigma reduction interventions. The current meta-analysis examines the effects of interventions on the cognitive, affective, and behavioral components of stigma around mental illness. Forty randomized controlled trials of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 56 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…A meta-analysis on interventions targeting public-stigma showed that both education and contact between people with and without MI (in the right context, e.g. no power differences) have positive effects on reducing stigma [53].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis on interventions targeting public-stigma showed that both education and contact between people with and without MI (in the right context, e.g. no power differences) have positive effects on reducing stigma [53].…”
Section: Discussionmentioning
confidence: 99%
“…The desire to be accepted overrides reasonable concern for one's mental health status, especially when those students do not understand what they are going through or how serious it is. Similarly, the fear of being exposed to having a mental illness may reduce the likelihood that struggling teens will discuss what they are going through [22].…”
Section: Social Dynamics During Adolescencementioning
confidence: 99%
“…This is because negative stereotypes lead to isolation and loneliness. In other words, teenagers might be more likely to refuse treatment due to concerns about being ostracized for their mental illness [22]. The language used to refer to mental illness impacts how the public views people with depression [29].…”
Section: Social Media and Depressionmentioning
confidence: 99%
See 2 more Smart Citations